2022
DOI: 10.1007/s11250-022-03181-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of sheep gastrointestinal nematodes on pasture in the tropical semiarid region of Brazil, using Bioverm® (Duddingtonia flagrans)

Abstract: We aimed to evaluate a Brazilian commercial formulation of the fungus Duddingtonia agrans (Bioverm®) for controlling gastrointestinal nematodes in sheep kept on native pasture in the Caatinga biome, in the semiarid region of Brazil. Twenty ewes, aged between 12 and 18 months, were divided into two groups. In the treated group, each animal received 1 g of the Bioverm® product for each 10 kg of live weight, daily, together with commercial feed, for six months. In the control group, the animals received feed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…and Oesophagostomum sp. In other studies, such as by Rodrigues et al [13] and Vieira et al [14] in southeastern Brazil, Haemonchus sp. was also the most prevalent.…”
Section: Resultsmentioning
confidence: 70%
“…and Oesophagostomum sp. In other studies, such as by Rodrigues et al [13] and Vieira et al [14] in southeastern Brazil, Haemonchus sp. was also the most prevalent.…”
Section: Resultsmentioning
confidence: 70%
“…The most significant effect has so far been shown by the fungus D. flagrans, 37.6-91.5% depending on the study (Szewc et al, 2021). For this reason, there is already a commercially available preparation based on this mushroom in Brazl, which has shown in vitro effectiveness against gastrointestinal nematodes of sheep, but also cattle and horses (Rodrigues et al, 2022). Furthermore, some strains of Bacillus thuringiensis that produce the insecticidal δ-endotoxin have shown high in vitro efficacy against adult H. contortus, T. colubriformis and O. circumcinta (Worku et al, 2017;Kotze et al, 2005).…”
Section: Biological Controlmentioning
confidence: 99%
“…The product Bioverm ® contains A. flagrans spores and is commercially available in Brazil. The product reduced the nematode egg counts per gram of faeces by around 75% in a recent 6-months study on controlling gastrointestinal nematodes in sheep (Rodrigues et al, 2022). Initial trials with potted crop plants and in greenhouses showed the potential of NTF against plant parasitic nematodes.…”
Section: Introductionmentioning
confidence: 98%